Moral Criticism Instead of Discussion - Baloun, Pavel; Gruber , Jan; Mareš, Jan; Strobach , Vít (Dějiny – teorie – kritika, 2013)
A reply to discussion contributions ZDENĚK R. NEŠPOR, Co chybí české (historické) vědě? Odpověď na „manifest“ čtyř mladých historiků (What is Czech (Historical) Science Lacking? Reply to the ‘Manifesto’ of Four Young Czech Historians), DTK 8/2012, No. 2, p. 297–304; JIŘI HANUŠ, Kritika kritiky neoliberalismu a ahistorických manifestů (A Criticism of a Critique of Neo-Liberalism and Ahistorical Manifestos), DTK 8/2012, No. 1, p. 145–148.